Endoscopic Treatment of Obesity - Agnieszka Swidnicka-Siergiejko; Eugeniusz Wróblewski; Andrzej Dabrowski (Canadian Journal of Gastroenterology)
BACKGROUND: The increasing incidence of obesity and overweight among children and adolescents will be reflected by the imminent increase in the number of obese patients who require more definitive methods of treatment. There is great interest in new, safe, simple, nonsurgical procedures for weight loss.